2019
DOI: 10.1176/appi.neuropsych.19020036
|View full text |Cite
|
Sign up to set email alerts
|

Moral Injury and PTSD: Often Co-Occurring Yet Mechanistically Different

Abstract: FIGURE 1 AND COVER. Recent studies have begun to explore how the underlying neurobiology of posttraumatic stress disorder (PTSD) may be affected by the nature of the index trauma. The results of a meta-analysis that grouped task-activated (trauma reminders) functional MRI (fMRI) studies by PTSD index trauma are color-coded by trauma type (blue, sexual/physical abuse; pink, combat-related) (1). Of note, although areas of greater activation were predominately in the right hemisphere for both groups, there was li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
128
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 74 publications
1
128
1
3
Order By: Relevance
“…These findings provide an overview of the complex comorbid relationships between PMIEs and PTSD symptoms. Whereas controversy regarding the relationships between PMIEs and PTSD (Barnes et al, 2019) remains, in our sample, MI-betrayal was found to be associated with the PTSD network through the NACM cluster. The strongest bridge edges were manifested between the MI-betrayal experience and the NACM cluster (See the bootstrapped centrality stability in the supplementary material).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…These findings provide an overview of the complex comorbid relationships between PMIEs and PTSD symptoms. Whereas controversy regarding the relationships between PMIEs and PTSD (Barnes et al, 2019) remains, in our sample, MI-betrayal was found to be associated with the PTSD network through the NACM cluster. The strongest bridge edges were manifested between the MI-betrayal experience and the NACM cluster (See the bootstrapped centrality stability in the supplementary material).…”
Section: Discussioncontrasting
confidence: 75%
“…A growing body of empirical evidence has indicated a direct association between PMIEs and PTSD symptoms, which may explain some of the high variability in the prevalence of PTSD among combatants, such as disease course and response to therapeutic interventions (Barnes, Hurley, & Taber, 2019;Steenkamp, Litz, Hoge, & Marmar, 2015). For example, recent studies found associations between perpetration and betrayal-based PMIEs and PTSD among active-duty Marines deployed to Afghanistan (Jordan et al, 2017) and among veterans from military conflicts in Iraq and Afghanistan (Currier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Practically, questions remain regarding best practices for treating moral injury and the extent to which current treatments for PTSD are suitable to treat moral injury (e.g. Barnes et al, 2019;Griffin et al, 2019;Neria and Pickover, 2019) or if new treatments designed specifically for moral injury would be more efficacious (e.g. Jordan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another potential consequence of both traumatic experiences, such as MST and combat, and nontraumatic experiences, including leadership failures and/or betrayal by peers, the military, or the government, is moral injury, which may result when individuals are confronted with events that violate their sense of right and wrong and lead to reactions including shame, guilt, and demoralization (Drescher, Foy, Kelly, Leshner, Schutz, & Litz, 2011; Frankfurt & Frazier, 2016). Although some researchers conceptualize moral injury as an exposure defined by committing or participating in transgressive acts (Frankfurt & Frazier, 2016), a growing body of research indicates that what is captured by the most widely used measure of moral injury, the Moral Injury Events Scale (MIES), may be better conceptualized as an outcome of exposure to these transgressions (Barnes, Hurley, & Taber, 2019), reflecting moral pain (e.g., guilt and shame) resulting from these experiences (Richardson et al., 2019). Although moral injury and PTSD often co‐occur, theoretical models of these two conditions differ (Litz et al., 2009) and have been shown to tap unique neural correlates (Barnes et al., 2019).…”
mentioning
confidence: 99%
“…Although some researchers conceptualize moral injury as an exposure defined by committing or participating in transgressive acts (Frankfurt & Frazier, 2016), a growing body of research indicates that what is captured by the most widely used measure of moral injury, the Moral Injury Events Scale (MIES), may be better conceptualized as an outcome of exposure to these transgressions (Barnes, Hurley, & Taber, 2019), reflecting moral pain (e.g., guilt and shame) resulting from these experiences (Richardson et al., 2019). Although moral injury and PTSD often co‐occur, theoretical models of these two conditions differ (Litz et al., 2009) and have been shown to tap unique neural correlates (Barnes et al., 2019). Posttraumatic stress disorder and its’ subsequent treatments are born from etiological models that primarily conceptualize PTSD as a fear‐based disorder, whereas moral injury encompasses constructs such as self‐blame and spiritual or existential issues that occur following witnessing or participating in events that conflict with deeply held moral beliefs (Litz et al., 2009).…”
mentioning
confidence: 99%